John Wesley’s Pneumatology and its application to the contemporary Ghanaian public space - Boaheng, Isaac (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
John Wesley, the founder of Methodism, made significant contribution to the subject of pneumatology. Wesley’s pneumatological teachings and praxis addressed a myriad of societal issues in eighteenth-century England, including moral decay, economic disparities, discrimination, superficial religion, and oppression. Contemporary Ghana (the context of this research) is confronted with socio-religious and political issues comparable to those of Wesley’s society. This situation has prompted this research which aims to apply relevant aspects of the socio-political ramifications of Wesley’s pneumatology for addressing Ghana’s socio-religious and political challenges. The research is a literature-based research that gathered data from such sources as books, journal articles and dissertations.  A comparative approach was used, where parallels were drawn between the two contexts to facilitate a contextual application Wesley’s pneumatology for the transformation of the Ghanaian public space. The central argument is that genuine Christian spirituality should extend beyond personal domains, actively engaging with and impacting the broader public sphere to yield a holistic societal transformation. Beyond its capacity to instigate ethical rejuvenation within Ghanaian society, this paper offers valuable insights into the subjects of Christian pneumatology and public theology.